1978
DOI: 10.1113/jphysiol.1978.sp012492
|View full text |Cite
|
Sign up to set email alerts
|

T‐tubule swelling in hypertonic solutions: a freeze substitution study.

Abstract: SUMMARYStriated muscles from Rana pipiens have been exposed for variable periods of time to Ringer solutions made hypertonic by addition of either sucrose or sodium chloride. The muscles have been rapid-frozen and then prepared for electron microscopy by either freeze-substitution, freeze-fracture or cryoultramicrotomy.The only compartment greatly affected by hypertonicity is the transverse tubular system, which is visibly swollen. None of the elements of the sarcoplasmic reticulum increase in size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 35 publications
1
33
1
Order By: Relevance
“…Almers et al (1981), using a more complete modelling, found that for frog muscle the volume of the fibre depleted of Ca was about 0-004 of the fibre volume, similar to the volume enclosed by the T-system (Peachey, 1965). In insect muscle fibres, the volume of the T-system may be somewhat greater since membrane capacity is higher than in frog muscle fibres of comparable diameter , and in the hypertonic solutions we use, the T-system is probably swollen (see Franzini-Armstrong, Heuser, Reese, Somlyo & Somlyo, 1978).…”
Section: Depletion May Contribute To Inactivation In Ba Solutionsmentioning
confidence: 74%
“…Almers et al (1981), using a more complete modelling, found that for frog muscle the volume of the fibre depleted of Ca was about 0-004 of the fibre volume, similar to the volume enclosed by the T-system (Peachey, 1965). In insect muscle fibres, the volume of the T-system may be somewhat greater since membrane capacity is higher than in frog muscle fibres of comparable diameter , and in the hypertonic solutions we use, the T-system is probably swollen (see Franzini-Armstrong, Heuser, Reese, Somlyo & Somlyo, 1978).…”
Section: Depletion May Contribute To Inactivation In Ba Solutionsmentioning
confidence: 74%
“…In intact muscle fibers, the transverse tubule component of the triad selectively swells by simple replacement of the external medium with hypertonic solutions of either sucrose or salt (47). The added solutes enter the t-system via the transverse tubule "mouth" or caveolae, causing an osmotic imbalance between the cytoplasmic compartment and lumen of the tubule.…”
Section: Susceptibility Of Triad Morphology To Salt Treatment or Osmomentioning
confidence: 99%
“…All the tabulated electron-probe data were obtained on unstained freeze-dried cryosections . After cryosections were obtained, the remaining portions of the muscles were processed by freeze substitution (for review, see references 10,29) for morphological studies.…”
Section: Methodsmentioning
confidence: 99%